Promoting Grammatical Awareness in English Language Teaching: ESP Context - Milawati, Milawati (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2021)
Recently, English Specific Purposes is taking a crutial issue to be considered. Since the implementation of ESP is apropriate to the need of its studies, the English skills which required by students is getting growth. Indeed, grammar as one of language components which supports the language skills also changing as its usage. However, the implementation of the grammar usage in ESP, is not really proper to its context. This paper presents the possibilities factors behind its unproper usage and also some activities which raises students’ grammar awarenes . By knowing more about those issue will not only help the teacher to lead the students more effectively and properly in using the grammar, but it will also provide the teacher with a means of evaluating the teaching learning process and help the teacher to produce activities that will actually motivate the students to learn. Keywords: Grammatical Awareness, ESP, English Language Teaching